Chinese famine exposure in early life and metabolic obesity phenotype in middle age: Results from the China health and retirement longitudinal study - Xu, Yunhan; Yi, Qian; Shan, Shiyi; Zhou, Jiali; Li, Shuting; Hou, Leying; Ye, Xinxin; Ying, Jiayao; Song, Peige; An, Lin (Frontiers in Endocrinology, 2022)
Objective: To assess the association between early life exposure to famine and the risk of metabolic obesity phenotypes among adults in middle age. Methods: The study selected two comparison groups. Comparison A consisted of a non-exposed group born between 1963-1965 from the China Health and Retirement Longitudinal Study (CHARLS) 2015 wave (N=862) and a fetal-exposed group born between 1959-1961 from the 2011 wave (N=507). Comparison B consisted of an early childhood-exposed group born between 1955-1957 from the 2011 wave (N=830) and a fetal-exposed group born between 1959-1961 from the 2015 wave (N=552). Multivariable logistic regressions were conducted to explore the associations between different periods of famine exposure and obesity, metabolic health status, and metabolic obesity phenotypes, with stratification by sex and famine severity. Results: Compared with the non-exposed group, participants exposed to famine in the fetal period had a significantly lower risk of overweight/obesity (OR: 0.75, 95%CI: 0.59-0.94) and a higher risk of metabolically unhealthy status (OR: 1.68, 95%CI: 1.31-2.15) and metabolically unhealthy non-obesity (MUNO) (OR: 2.16, 95%CI: 1.51-3.11) at the age of 50-52 years. In the sex-stratified analysis, males exposed to famine in the fetal period had a significantly lower risk of overweight/obesity (OR: 0.60, 95%CI: 0.44-0.81) and metabolically unhealthy non-obesity (MHO) (OR: 0.59, 95%CI: 0.39-0.88), while such associations were not found in females. Compared with the early childhood exposure group, participants in the fetal exposure group had a significantly lower risk of metabolic unhealthy status (OR: 0.66, 95%CI: 0.52-0.85) and MUNO (OR: 0.51, 95%CI: 0.36-0.73). Those associations were observed in both males and females. Conclusion: Exposure to famine in early life increased the risk of metabolically unhealthy status in adulthood. Different metabolic subtypes should be identified at an early stage and followed by classification, intervention and treatment.